2015
DOI: 10.14257/ijca.2015.8.10.27
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Formula of Cutting Force Established in Turning High Temperature Alloy

Abstract: In order to study the experiential formula of cutting force and the influence of each cutting parameter for turning superalloy GH4169, the orthogonal experiment is applied to coated carbide tools turning high-temperature alloy GH4169, and got empirical formula of cutting force carbide using cutting tools for turning superalloy GH4169. The results show that: the greatest impact on the cutting force factor decreases in the order of the cutting depth, feed and cutting speed influence on the test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The turning force 2 mainly comes from the following two aspects: first, the elastic and plastic deformation resistance 4 produced by the three deformation zones; second, the friction force between the chip, the workpiece, and the tool. The turning force F can be decomposed into three mutually perpendicular forces, as shown in Figure 1: the main turning force F c , whose direction is perpendicular to the base plane and in line with the cutting speed V c direction; the radial force F r , whose direction is perpendicular to the feed direction in the base plane; and the feed force F f , whose direction is parallel to the feed direction in the base plane.…”
Section: Turning Forcementioning
confidence: 99%
See 1 more Smart Citation
“…The turning force 2 mainly comes from the following two aspects: first, the elastic and plastic deformation resistance 4 produced by the three deformation zones; second, the friction force between the chip, the workpiece, and the tool. The turning force F can be decomposed into three mutually perpendicular forces, as shown in Figure 1: the main turning force F c , whose direction is perpendicular to the base plane and in line with the cutting speed V c direction; the radial force F r , whose direction is perpendicular to the feed direction in the base plane; and the feed force F f , whose direction is parallel to the feed direction in the base plane.…”
Section: Turning Forcementioning
confidence: 99%
“…The prediction of static turning force mainly includes the finite element method, the analytical modeling method, and the empirical formula method. 14 These methods have their advantages in predicting the static turning force. But the premise of its prediction is to analyze the existing turning force data and get the corresponding model, so as to find out the relationship between turning force and some parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The most influential factor which can affect the cutting force is feed rate. FY Yu et al 11 established the empirical model of cutting force of turning superalloy Inconel718 with coated carbide tools. The results showed that the factors which exert impact on the cutting force in the decreasing order are as follows: the cutting depth, feed, and cutting speed.…”
Section: Introductionmentioning
confidence: 99%